The Inclusion of Alhagi maurorum in Growing Camel Diet: Effect on Performance, Liver-Related Blood Metabolites, and Antioxidant Status - Ghavipanje, Navid; Vargas-Bello-Pérez, Einar; Afshin, Mojtaba; Hosseini, Seyyed Ahmad; Aghashahi, Alireza; Vatankhah, Amir Mansour (Frontiers in Veterinary Science, 2022)
This study determined the effect of dietary inclusion of camelthron (Alhagi maurorum, AM) on performance, blood metabolites and antioxidant status of growing camels. Eighteen Sindi camel calves with 9–10 months of age and 115 ± 7 kg body weight (BW) were randomly assigned to three diets (with forage:concentrate ratio of 50:50) that were formulated by partial and total substitution of alfalfa hay with AM as follows: (1) diet without AM (control), (2) diet containing 25% of AM (AM-25), and (3) diet containing 50% of AM (AM-50) (dry matter basis) for 150 days. Dry matter intake (DMI) was recorded daily. The camels were weighed individually on days 0, 30, 60, 90, 120, and 150. Blood samples were collected on days 0, 75, and 150. DMI were increased (p = 0.004) with AM-50 feeding followed by AM-25. Total weight gain (p = 0.048) and average daily gain (ADG) (p = 0.043) decreased with AM-50; however, no differences were observed between AM-25 and CON groups. Feed cost per kg BW gain tended to decrease (p = 0.092) and return per kg BW gain tended to increase (p = 0.087) by AM feeding. The plasma triglycerides (TG) (p = 0.046) and cholesterol (CHOL) (p = 0.025) concentration were reduced with AM inclusion. Additionally, the AM50-fed camels showed the lowest concentration of aspartate aminotransferase (AST) (p = 0.008) and alanine aminotransferase (ALT) (p = 0.0036), followed by AM-25. The plasma malondialdehyde (MDA) were depressed (p = 0.037) and total antioxidant capacity (TAC) were enhanced (p = 0.016) with both AM-25 and AM-50. Moreover, feeding the AM containing diets led to higher (p = 0.004) glutathione peroxidase (GPx) along with a tendency for superoxide dismutase (SOD) (p = 0.075) and catalase (CAT) (p = 0.094). Overall, feeding camels with AM up to 25% DM of diet positively influenced the antioxidant status without severe deleterious effects on performance.